Main mechanisms typification of world salt tectonics: Verkhnekamskoe deposit as standard of multi-stage gravitational sliding - Tchaikovski, I. (Perm Federal Research Centre Journal, 2013)
We provided review and typification of the main types of salt structures, genesis of which are connected with action of six mechanisms: 1) gravity advection (salt dome tectonics, Trusheim’ halokinesis, Jackson’s active diapirism); 2) gravity advection provoked by a cross bending and upper- salt thickness expansion (salt dome tectonics connected with block motions in basement, Jackson’s reactive diapirism); 3) longitudinal compression (Mrazek’s diapirism, compression salt tectonics); 4) laminated strike-slip with shearing-off (shearing tectonic of the Jurassic type); 5) gravity current and gliding (gravity gliding tectonic); 6) salt dissolving (tectonic of salt structure degradation).Comparison of mechanisms of the main tectonic events shown on the Verkhnekamskoe deposit with assigned tectonic types allows to suggest that at the end of the bereznikovskoe time there was a salt body slipping to the center of the Solikamskaya basin like the Iranian salt glaciers, during the sheshminsky time – formation of contemporaneous strike-slip faults of Durinsky and Borovitsky troughs, and in Pleistocene – slipping of upper-salt thickness along the salt table like shearing tectonic of the Jurassic type. However in all cases the main mechanism was gravity sliding which in time was displaced from a salt deposit bottom to its roof.